Rights of the accused in the Islamic legislation: a comparative and analytical study - Muhammad Husni, Ahmad; Muhammad Husni, Amin; Nasri, Mohd Sabree (Scholars Middle East Publishers, UAE, 2019)
This study aims to shed light on the extent to which the accused’s right in Islamic jurisprudence is in harmony with the conventional law. The accused may be exposed to some harmful acts during his trial which may entirely affect his rights which will give him the entitlement to defend himself. The researcher pays attention to explaining the rights of the accused person in Islamic jurisprudence compared to the conventional law. The study adopts inductive approach to gather information written in Islamic jurisprudence, and adopts comparative approach in order to make comparisons between the views of ancient and contemporary jurists in question under discussion, and transfer ideas of Shariah experts to the legal studies field in order to compare the approach and benefit and vice versa. The study concludes that the conventional law does not differ much from the Islamic jurisprudence in terms of providing personal rights to the accused; both Islamic jurisprudence and conventional law agree on the principle that the accused is innocent until proven guilty.